Expelled ebook - Patterson, James (2017)
When four teens are accused of crimes they didn't commit, they team up to investigate everyone at school who could have set them up. Theo Foster's Twitter account used to be anonymous—until someone posted a revealing photo that got him expelled. No final grade. No future. No fair . Theo's resigned to a life of misery working at the local mini-mart when a miracle happens: Sasha Ellis speaks to him. Sasha Ellis knows his name. She was also expelled for a crime she didn't commit and now he has the perfect way to get her attention: find out who set them up. To uncover the truth, Theo has to get close to the suspects: the hacker, the quarterback, the mean girl, the vice principal, and his own best friend. What secrets are they hiding? And how can Theo catch their confessions on camera?